Liver injury in patients with severe acute respiratory syndrome coronavirus-2 infection: a systematic review and meta-analysis. Issue 9 (September 2021) - Labenz, Christian; Toenges, Gerrit; Wörns, Marcus-Alexander; Sprinzl, Martin F.; Galle, Peter R.; Schattenberg, Jörn M.
Abstract : Objective: Coronavirus disease-19 (COVID-19) infection is a global health threat. To inform the liver community on the potential relevance of COVID-19, we performed a systematic review and meta-analysis of published data on liver injury in patients with COVID-19 infection. Methods: We searched PubMed and Google Scholar through 22 March according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Pooled data were analyzed by using random-effects meta-analyses. Results: A total of 14 studies combining data from 2.871 patients were identified. The prevalence of pre-existing liver disease was reported at 3.1%. The pooled prevalence of elevated aspartate aminotransferase (AST) and alanine transaminase (ALT) levels were 26% [95% confidence interval (CI), 20–32%] and 19% (95% CI, 14–26%), respectively. Only two studies reported the prevalence of elevated liver function tests according to normal ward versus ICU and here the frequency of elevated levels of AST was 50% and 62% versus ALT 40.8% and thus quantitatively higher in ICU-treated patients. Mean levels of absolute AST levels were 33 U/L (95% CI, 30.21–36.09), while mean ALT levels were 31 U/L (95% CI, 27.52–34.57). Cholestatic liver function tests were only incompletely reported in 510 patients. Here, mean levels of alkaline phosphatase were 71 U/L across three studies, and mean levels of gamma-glutamyl transferase were 40.6 U/L across four studies. Conclusions: Emerging data on LFTs in COVID-19 are heterogeneous indicating mild LFTs involvement in every fourth to fifth patients with numerical more prevalent AST over ALT elevations. Prospective studies are needed to define the clinical relevance of liver injury in COVID-19. Abstract : Supplemental Digital Content is available in the text.